Breast cancer follow-up after a primary diagnosis: A confused picture. (August 2019) - Cruickshank, Susanne; Barber, Matthew
Abstract: The follow-up care of people diagnosed with early breast cancer varies across the world. In the UK, services have evolved in an ad hoc way, with no standardized approach nationally. Some people are seen face to face at regular intervals, others are discharged at two years, while others are followed up over the telephone. This is creating confusion for patients as to what is best practice. The lack of evidence to support intensive surveillance is frequently cited as the main reason to reduce or indeed review the benefits of face to face clinical consultations in the hospital/community setting. In addition, a lack of specific recommendations in current guidelines compounds this. Although primary disease stage and treatment are strong indicators of survival, and time to recurrence (both local and distant) is extending, patterns of follow-up care in the UK differ depending on where you live. Yet, European and American guidelines, where survival is frequently reported as being better than the UK, continue to recommend follow-up at regular intervals as part of their overall management approach; to ensure new and changing ways of treating early breast cancer are initiated, managed and monitored accordingly. Indeed their guidelines are increasing rather than decreasing follow-up. While their health systems may differ, survival outcome reporting is not adjusted to reflect these differences. This paper provides an overview of breast cancer follow-up guidance across the world and opens up a debate about whether patterns of follow up care will affect survival outcomes into the future. Highlights: Breast cancer guidelines across the world differ in relation to follow-up practice. There is a lack of consensus globally as to how, when and by whom, follow up care is provided. The treatments available for early breast cancer require long-term monitoring. Patients receive different follow-up approaches dependent on where they live.